Efforts to Withdraw Inheritance Assets Controlled by One of the Heirs - Dewanto Satrio Prakoso; Arauna, El-Roi; Tri Budhayati, Christiana (JUSTISI, 2025)
This study aims to explain the efforts that can be used by aggrieved heirs to withdraw the inheritance property controlled by one of the heirs due to a will made under duress. The research method used is normative legal research using the statutory approach method and conceptual approach method. Novelty in this research is to provide the most appropriate effort in withdrawing inherited property controlled by one of the heirs, this novelty includes important elements that will contribute to science, especially in the field of inheritance law. Meanwhile, people only withdraw inherited property using the inheritance law approach. The research shows that there are various efforts to withdraw the inheritance controlled by another heir such as the Right of Hereditatis Petitio, the right to demand the distribution of inheritance, and unlawful acts. The author concludes, taking into account the advantages and disadvantages of each of these efforts, that the effort through the right of hereditatis petitio is the most appropriate effort to withdraw inherited property controlled by one of the heirs.